Children’s Syntactic Competence at Age 6.5–7.5 Years (Based on Utterances with Verbs of Motion) - Siudzińska, Natalia; Brzeszkiewicz, Kamila (Slavistica Vilnensis, 2020)
The article is devoted to selected issues associated with acquiring syntax competence by children who are beginning early school education. The principal aim of the article is to demonstrate how children at this age attain sentence structures constituted by verbs of movement. The feature of the selected predicates is the fact that they open a position for the biggest out of all verb classes number of positions opened by a predicate (an agent, three locative positions, an object, a tool), which gives an opportunity to view the process of acquiring syntax competence by children. Sentences with verbs of movement, chosen form utterances of children whose task was to describe situations presented in illustrations, served as the material for the research. Studies have shown that children aged between six and a half to seven and a half were able to employ the verbs of movement and the proper syntactic structure appropriately in the given circumstances. Two-position structures (single, undeveloped sentences) dominated the collected data, indicating that children create short and precise messages, naming only what is most important for them in the illustration (i.e. what they considered to be the subject of the statement). The children employed all syntactic positions. The most frequently employed positions were LOCATOR [which way] in the verbs of linear movement, TOOL and OBJECT in the phrasal verbs. The LOCATOR [from] was the least employed position. The study demonstrated that syntax development is inextricably linked to the increase in the number of words in the child’s active vocabulary. The evidence for the above statement was derived from the errors resulting from the limited amount of lexical resources acquired by children within this age group. The children did not show any major problems when it came to employing inflected forms of words. The problem was only the correct use of prepositions, especially in the context of employing the LOCATOR position [which way]. The examination findings have confirmed the presuppositions of the authors that despite the diversity of syntax positions this class of verbs is mastered fairly well by children at this age.